New frontier, new power: the retail environment in Australia's dark market. (26th November 2003) - Carter, S M
Abstract : Objective: To investigate the role of the retail environment in cigarette marketing in Australia, one of the "darkest" markets in the world. Design: Analysis of 172 tobacco industry documents; and articles and advertisements found by hand searching Australia's three leading retail trade journals. Results: As Australian cigarette marketing was increasingly restricted, the retail environment became the primary communication vehicle for building cigarette brands. When retail marketing was restricted, the industry conceded only incrementally and under duress, and at times continues to break the law. The tobacco industry targets retailers via trade promotional expenditure, financial and practical assistance with point of sale marketing, alliance building, brand advertising, and distribution. Cigarette brand advertising in retail magazines are designed to build brand identities. Philip Morris and British American Tobacco are now competing to control distribution of all products to retailers, placing themselves at the heart of retail business. Conclusions: Cigarette companies prize retail marketing in Australia's dark market. Stringent point of sale marketing restrictions should be included in any comprehensive tobacco control measures. Relationships between retailers and the industry will be more difficult to regulate. Retail press advertising and trade promotional expenditure could be banned. In-store marketing assistance, retail–tobacco industry alliance building, and new electronic retail distribution systems may be less amenable to regulation. Alliances between the health and retail sectors and financial support for a move away from retail dependence on tobacco may be necessary to effect cultural change.